Chronic Toxoplasma gondii Infection Exacerbates Secondary Polymicrobial Sepsis - Souza, Maria C.; Fonseca, Denise M.; Kanashiro, Alexandre; Benevides, Luciana; Medina, Tiago S.; Dias, Murilo S.; Andrade, Warrison A.; Bonfá, Giuliano; Silva, Marcondes A. B.; Gozzi, Aline; Borges, Marcos C.; Gazzinelli, Ricardo T.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Sepsis is a severe syndrome that arises when the host response to an insult is exacerbated, leading to organ failure and frequently to death. How a chronic infection that causes a prolonged Th1 expansion affects the course of sepsis is unknown. In this study, we showed that mice chronically infected with Toxoplasma gondii were more susceptible to sepsis induced by cecal ligation and puncture (CLP). Although T. gondii-infected mice exhibited efficient control of the bacterial burden, they showed increased mortality compared to the control groups. Mechanistically, chronic T. gondii infection induces the suppression of Th2 lymphocytes via Gata3-repressive methylation and simultaneously induces long-lived IFN-γ-producing CD4+ T lymphocytes, which promotes systemic inflammation that is harmful during CLP. Chronic T. gondii infection intensifies local and systemic Th1 cytokines as well as nitric oxide production, which reduces systolic and diastolic arterial blood pressures after sepsis induction, thus predisposing the host to septic shock. Blockade of IFN-γ prevented arterial hypotension and prolonged the host lifespan by reducing the cytokine storm. Interestingly, these data mirrored our observation in septic patients, in which sepsis severity was positively correlated to increased levels of IFN-γ in patients who were serologically positive for T. gondii. Collectively, these data demonstrated that chronic infection with T. gondii is a critical factor for sepsis severity that needs to be considered when designing strategies to prevent and control the outcome of this devastating disease.